Study of Bacillus spp. strains used in the production of γ-polyglutamic acid in submerged culture - Campos, V. [UNESP]; Pimentel Filho, N. J.; Medeiros, T. A.M. [UNESP] (My University, 2020)
Gamma-polyglutamic (γ-polyglutamic) acid has received considerable attention for environmental applications. γ-polyglutamic acid can be produced by fermenting soybeans and by submerged culture using the bacterium Bacillus subtilis. Although it is practically impossible to chemically synthesise γ-polyglutamic acid, this biopolymer can be obtained through microbial culture. The microorganism most commonly used in the production of γ-polyglutamic acid, among other strains, is B. subtilis, which has been investigated for the production of biopolymers. The purpose of the present work was to evaluate the production of γ-polyglutamic acid from submerged culture of different Bacillus strains. The evaluation of the efficiency of Bacillus strains in producing γ-polyglutamic acid indicated that B. licheniformis produced a higher volume of the biopolymer than B. subtilis. The highest γ-polyglutamic acid production by B. licheniformis was 398.1 mg L-1. B. licheniformis was found to be an L-glutamic acid-independent bacterium for the production of γ-polyglutamic acid. B. licheniformis and B. subtilis growth and γ-polyglutamic acid production rates were also influenced by the culture media.
Keywords: Genus bacillus; Microorganisms; Soybean fermentation; Submerged culture; γ-polyglutamic acid